Autonomous Transaction Model for E-Commerce Management Using Blockchain Technology - Sekar S. (19517647) (2022)
Abstract A blockchain is an advanced technology that can power over a decentralized network. The authors bring it up to design the autonomous transaction system for e-commerce applications; because of the dramatic increase in IoT devices, communication between physical things is enabled. This brings more efficiency and accuracy, which benefits the outsiders while human interaction reduces. There is a big challenge in data storage after payment in the e-commerce application. Blockchain presents an appropriate platform for the distributed data storage; it also protects the data from outsiders. The authors create blocks that check and record each transaction that took place in the e-commerce application. Blockchain is going to protect the user's privacy from outsiders/banks that are being violated. The authors deliver this research in this paper in terms of the method with detailed design and full implementation. The system captures the user data, processes it, and gives a visual representation of the processed data. Other Information Published in: International Journal of Information Technology and Web Engineering License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.4018/ijitwe.304047